2023
DOI: 10.2147/ndt.s394438
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Metabolic Score for Insulin Resistance and Symptomatic Intracranial Hemorrhage in Ischemic Stroke Patients After Endovascular Thrombectomy

Abstract: Background and Purpose Insulin resistance plays a pivotal role in the pathophysiology of ischemic stroke. This study aimed to determine the relationship between the novel metabolic score for insulin resistance (METS-IR) and symptomatic intracranial hemorrhage (sICH) after endovascular thrombectomy (EVT) in stroke patients. Methods We retrospectively included patients with large artery occlusion in the anterior circulation and treated by EVT from 2 stroke centers (Nanjin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Considering the practicality of its measurements and the pathophysiological correlations with components of metabolic syndrome and IR, a predictive role of METS-IR has also been highlighted in endothelial dysfunction and inflammatory [ 11 , 12 ]. Moreover, accumulative evidence suggested that METS-IR was related to cardiometabolic disorders and cardiovascular diseases (CVDs) [ 13 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Considering the practicality of its measurements and the pathophysiological correlations with components of metabolic syndrome and IR, a predictive role of METS-IR has also been highlighted in endothelial dysfunction and inflammatory [ 11 , 12 ]. Moreover, accumulative evidence suggested that METS-IR was related to cardiometabolic disorders and cardiovascular diseases (CVDs) [ 13 18 ].…”
Section: Introductionmentioning
confidence: 99%